2021
DOI: 10.1080/01140671.2021.1966480
|View full text |Cite
|
Sign up to set email alerts
|

Moths as potential pollinators in avocado (Persea americana) orchards in temperate regions

Abstract: Avocado (Persea americana) flowers are primarily diurnal, however low minimum overnight temperatures can delay in the opening of female-phase flowers such that the flowers open late in the day and remain open overnight. To determine whether moths are important visitors to avocado flowers at night, we trapped moths in the Bay of Plenty, New Zealand, and examined the pollen moths carried. 11.5% of moths carried avocado pollen grains, and 50.4% of all moths were found to carry pollen grains from other plant speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Clearly camera surveillance can provide a temporally representative view of flower visitation [ 27 ], which is difficult to achieve through visual observations [ 15 ]. Pollen microscopy and DNA metabarcoding reveal the types of pollen carried by nocturnal insects [ 14 , 16 , 25 ], while exclusion experiments establish which agricultural plants depend on nocturnal pollination [ 13 ]. However, the scale of nocturnal pollination has proven particularly difficult to quantify [ 17 ], and cameras can provide robust estimates of relative visitation by day- and night-active pollinators [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly camera surveillance can provide a temporally representative view of flower visitation [ 27 ], which is difficult to achieve through visual observations [ 15 ]. Pollen microscopy and DNA metabarcoding reveal the types of pollen carried by nocturnal insects [ 14 , 16 , 25 ], while exclusion experiments establish which agricultural plants depend on nocturnal pollination [ 13 ]. However, the scale of nocturnal pollination has proven particularly difficult to quantify [ 17 ], and cameras can provide robust estimates of relative visitation by day- and night-active pollinators [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…moths, are particularly poorly understood, despite facing additional threats from artificial light at night [9][10][11][12]. Evidence is mounting on the agricultural and economic importance of nocturnal pollination, and recent studies showing how apples [13] and avocados [14] benefit from flower visits at night. Still, it remains difficult to generate rigorous, like-for-like comparisons between dayand night-time pollinators [15,16] and too little is known about the scale of nocturnal pollination [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of these are: bumble bees ( Bombus spp. ; Cutting et al, 2018; McBrydie et al, 2017), solitary bees (Broussard et al, 2011), and non‐bee taxa such as butterflies (Rasheed et al, 2015), flies (Cook et al, 2020; Howlett & Gee, 2019; Stavert et al, 2018) and moths (Buxton et al, 2021; Manning & Cutler, 2013; Pattemore et al, 2018), yet all of these insect groups are still understudied compared with honey bees (Rader et al, 2016). Other understudied pollinators include vertebrates such as birds, lizards and mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Cutler et al, 2012); thus their contribution to the pollination of crop or medicinally important plants remains largely unknown and may be under‐represented in the literature (Buxton et al, 2018; Macgregor & Scott‐Brown, 2020). There is, however, a growing appreciation that nocturnal insects (particularly moths) may be contributing substantially to the pollination of commercially important crops such as apples (Robertson et al, 2021), avocado (Buxton et al, 2021), and gourds (Lu et al, 2021) making this area of research very timely.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CropPol potentially underestimates the contribution of nocturnal pollination. For instance, this global database does not record nocturnal pollination of apple and cucurbits; however, recent exclusion experiments showed that the contribution of nocturnal pollinators to pollination is significant [28][29][30].…”
Section: Nocturnal Pollinators Are Neglectedmentioning
confidence: 99%